Fabrication of oriented NV center arrays in diamond via femtosecond laser writing and reorientation - Klink, Kai; Kirkpatrick, Andrew Raj; Tadokoro, Yukihiro; Becker, Jonas Nils; Nicley, Shannon Singer (Frontiers in Quantum Science and Technology, 2025)
IntroductionNitrogen-vacancy (NV) centers in diamond are widely recognized as highly promising solid-state quantum sensors due to their long room temperature coherence times and atomic-scale size, which enable exceptional sensitivity and nanoscale spatial resolution under ambient conditions. Ultrafast laser writing has demonstrated the deterministic spatial control of individual NV− centers, however, the resulting random orientation of the defect axis limits the magnetic field sensitivity and signal contrast.MethodsWe developed an all-optical approach for reorienting laser-written NV− centers to lie along a specific crystallographic axis using femtosecond laser annealing. The orientation is determined by polarization analysis, and the annealing and subsequent polarization analysis are repeated until the desired orientation is observed.ResultsOur method achieves deterministic alignment of NV− centers along the optical axis in (111)-oriented diamond substrates and allows selection between two observable orientation classes in (100)-oriented substrates. The reorientation preserves spatial ordering while producing uniform orientation across arrays of NV− centers.DiscussionThis approach enables scalable fabrication of orientation-controlled NV− arrays, and paves the way for scalable, high performance quantum devices based on orientation-controlled NV− centers.